Lacticaseibacillus rhamnosus HM126 Alleviates Allergic Rhinitis by Modulating the Intestinal Flora and Metabolites in Mice - YUAN Xueping, ZHAO Yujin, LI Xianping, ZHANG Yu, LI Xiaojing, YAO Chunyu, TANG Mi, LIU Lu, ZHAO Junying, QIAO Weicang, GAO Ziqing, CHEN Lijun (Shipin Kexue, 2025)
We investigated the role of Lacticaseibacillus rhamnosus HM126 in the prevention and alleviation of ovalbumin-induced allergic rhinitis (AR) in mice. We also analyzed the composition of the gut microbiota and the differences in metabolite profile using 16S rRNA gene sequencing and untargeted metabolomics, respectively. The results showed that the nasal symptoms of AR mice were significantly reduced and the nasal function was restored to normal after intervention with L. rhamnosus HM126. The correlation analysis between the gut flora and metabolome revealed that this strain could alleviate AR symptoms by modulating the relative abundance of the gut flora and inducing an increase in metabolites such as quinic acid, leptomycin b, ketoprofen, 18 alpha-glycyrrhetinic acid, and asiatic acid. This study suggested that L. rhamnosus HM126 can ameliorate allergic inflammatory response by regulating gut microbiota dysbiosis and producing immunomodulatory substances in mice, providing theoretical support for the alleviation of AR by probiotics.